2005
DOI: 10.1002/cncr.21330
|View full text |Cite
|
Sign up to set email alerts
|

Treatment decision‐making strategies and influences in patients with localized prostate carcinoma

Abstract: The chin, or mentum osseum, is one of the most distinctive anatomical traits of modern humans. A variety of hypotheses for the adaptive value of the chin have been proposed, ranging from mechanical stress resistance to sexual selection via mate choice. While the sexual selection hypothesis predicts dimorphism in chin shape, most biomechanical hypotheses preclude it. Therefore determining the presence or absence of significant sexual dimorphism in chin shape provides a useful method for differentiating between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
97
1
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 73 publications
11
97
1
2
Order By: Relevance
“…Many of the patients perceived their cancer as a localised problem and that the most tangible and definitive method of curing or preventing the disease from spreading was to remove the tumour [27-29, 31, 35]. These findings were also replicated in three of the quantitative studies, which reported that beliefs about the effectiveness of surgery and complete tumour removal were statistically associated with selecting surgery [33][34][35]. Surgery would also allow for surgeons to be more informed about the nature and extent of the cancer and would provide the patients with more information about their disease [27,28].…”
Section: Radical Prostatectomymentioning
confidence: 95%
See 1 more Smart Citation
“…Many of the patients perceived their cancer as a localised problem and that the most tangible and definitive method of curing or preventing the disease from spreading was to remove the tumour [27-29, 31, 35]. These findings were also replicated in three of the quantitative studies, which reported that beliefs about the effectiveness of surgery and complete tumour removal were statistically associated with selecting surgery [33][34][35]. Surgery would also allow for surgeons to be more informed about the nature and extent of the cancer and would provide the patients with more information about their disease [27,28].…”
Section: Radical Prostatectomymentioning
confidence: 95%
“…Patients' beliefs and other influences in selecting to undergo a radical prostatectomy were clearly reported in nine of the studies [27][28][29][30][31][32][33][34][35]. Many of the patients perceived their cancer as a localised problem and that the most tangible and definitive method of curing or preventing the disease from spreading was to remove the tumour [27-29, 31, 35].…”
Section: Radical Prostatectomymentioning
confidence: 99%
“…Medical decision making for PC is difficult. Sometimes for professionals, often for patients [12,26]. It is important to keep in mind that the individual patient may or may not feel comfortable with the responsibility of choosing between the available treatment options and too much encouragement towards active involvement in TDM may lead to unwanted control [27].…”
Section: Practice Implicationsmentioning
confidence: 99%
“…[9][10][11][12] However, little is known about patients' actual participation in TDM. As it has been demonstrated that cancer patients' preferred and assumed roles in TDM match in approximately 35-65% of the cases [13][14][15][16][17], role preferences are not a reliable indication of patients' level of participation.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In addition, urinary and sexual function are known to worsen with age 5 and functional and health-related quality of life (HRQOL) outcomes are of great importance for young men treated with curative intent for prostate cancer. 6,7 Urinary and sexual bother, or distress, after radical prostatectomy (RP) may be different for younger men if they have better baseline urinary and sexual function. For example, if younger men have higher baseline function, then any decrease in function may be associated with more significant bother than in older men.…”
Section: Introductionmentioning
confidence: 99%